Hymenoscyphus fraxineus is a leaf pathogen of local Fraxinus species in the Russian Far East. (11th August 2016) - Drenkhan, R.; Solheim, H.; Bogacheva, A.; Riit, T.; Adamson, K.; Drenkhan, T.; Maaten, T.; Hietala, A. M.
Abstract : Dieback of European ash was first observed in Europe in the early 1990s. The disease is caused by the invasive ascomycete Hymenoscyphus fraxineus, proposed to originate from Far East Asia, where it has been considered a harmless saprotroph. This study investigates the occurrence of H. fraxineus in tissues of local ash species in the Russian Far East, and assesses its population‐specific genetic variation by ITS sequencing. Shoot dieback symptoms, characteristic of H. fraxineus infection on European ash, were common, but not abundant, on Fraxinus mandshurica and Fraxinus rhynchophylla trees in Far East Russia. High levels of pathogen DNA were associated with necrotic leaf tissues of these ash species, indicating that the local H. fraxineus population is pathogenic to their leaves. However, the low levels of H. fraxineus DNA detected in shoots with symptoms, the failure to isolate this fungus from such tissues, and the presence of other fungi with pathogenic potential in shoots with symptoms indicate that local H. fraxineus strains may not be responsible (or their role is negligible) for the observed ash shoot dieback symptoms in the region. Conspicuous differences in ITS rDNA sequences detected between H. fraxineus isolates from Russian Far East and European populations suggest that the current ash dieback epidemic in Europe might not directly originate from the Russian Far East. Revision of the herbarium material shows that the earliest specimen of H. fraxineus was collected in 1962 from the Russian Far East and the oldest H. fraxineus specimen of China was collected in 2004.